2008
DOI: 10.1016/j.ijsolstr.2008.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Bounds for shakedown of cohesive-frictional materials under moving surface loads

Abstract: In this paper, shakedown of a cohesive-frictional half space subjected to moving surface loads is investigated using Melan's static shakedown theorem. The material in the half space is modelled as a Mohr-Coulomb medium. The sliding and rolling contact between a roller and the half space is assumed to be plane strain and can be approximated by a trapezoidal as well as a Hertzian load distribution. A closed form solution to the elastic stress field for the trapezoidal contact is derived, and is then used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Boulibane et al (2005) similarly found the pavement strength limited the ultimate capacity above a certain thickness. This limit increased significantly with the angle of shearing resistance of the pavement (corroborated by cohesive-frictional shakedown analysis by Zhao et al, 2008, which found the result to be highly sensitive to the angle of shearing resistance), but was influenced little by its cohesion. These analyses indicate the load-spreading properties of the pavement layers, dictated by the material quality, to be critical to governing whether shakedown or progressive failure occurs.…”
Section: Pmentioning
confidence: 68%
See 1 more Smart Citation
“…Boulibane et al (2005) similarly found the pavement strength limited the ultimate capacity above a certain thickness. This limit increased significantly with the angle of shearing resistance of the pavement (corroborated by cohesive-frictional shakedown analysis by Zhao et al, 2008, which found the result to be highly sensitive to the angle of shearing resistance), but was influenced little by its cohesion. These analyses indicate the load-spreading properties of the pavement layers, dictated by the material quality, to be critical to governing whether shakedown or progressive failure occurs.…”
Section: Pmentioning
confidence: 68%
“…The concept of shakedown and progressive plastic failure can be applied to the interaction between the road and subgrade. Various authors have modelled road structures as layers of elastic-perfectly plastic material (Sharp and Booker 1984;Boulibane et al 2005;Zhao et al 2008) and found initial plasticity followed by shakedown is possible for loads initially causing local yield if a residual stresses field can develop to counteract yielding (in both the pavement and subgrade). Sharp and Booker (1984) found stiffer pavement layers increases the failure load for the subgrade but reduces the failure load for the pavement; increasing pavement stiffness beyond an optimal value can decrease its capacity.…”
Section: Pmentioning
confidence: 99%
“…Field observations indicated that many pavements do in fact shakedown rather than deform continuously [14]. 5…”
Section: B)mentioning
confidence: 99%
“…And later, this method was extended for the nonassociated plastic flow materials. 15 Zhao et al 16 developed a numerical technique to calculate the shakedown limit of the Mohr-Coulomb material under moving surface loads in the plane strain condition. Yu and Wang 17 developed a rigorous lower bound solution to the 3D pavement shakedown problem by searching for a critical self-equilibrated residual stress field using an optimization procedure, and was then further extended to consider more realistic cases of layered pavements and anisotropic behavior of the pavement materials.…”
Section: Introductionmentioning
confidence: 99%